Kepemilikan Manajerial Dalam Memoderasi Leverage Dan Aktivitas Usaha Terhadap Profitabilitas - Marella Cahya Rini; I Gusti Ngurah Agung Suaryana (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
The purpose of this paper is to find out how the financial performance of the property and real estate sector companies on the Indonesia Stock Exchange for the 2017-2022 period in terms of leverage, business activity, and profitability. And find out how leverage and business activity influence the profitability of the observed company with managerial ownership as a moderator. There are 90 samples taken from the financial statements of 15 companies for 6 periods from 2017-2022. The data analysis technique used is Moderated Regression Analysis (MRA). The results of the analysis show that leverage have no significant effect on profitability, business activity had a positive effect on profitability, managerial ownership weakens the positive effect of leverage on profitability, and managerial ownership strengthens the positive effect of business activity on profitability.